IJABE has successfully been covered and indexed in Thomson Reuter’s Web of Science Core Collection - Yingkuan, Wang (International Journal of Agricultural and Biological Engineering, 2014)
DOI: 10.3965/j.ijabe.20140704.001Citation: Wang Y K. IJABE has successfully been covered and indexed in Thomson Reuter’s Web ofScience Core Collection. Int J Agric & Biol Eng, 2014; 7(4): 01－02.I received a formal letter in late July which was signed by Marian Hollingsworth, the Publisher RelationsDirector of Thomson Reuters, which confirmed that the International Journal of Agricultural andBiological Engineering (IJABE) has been selected for complete coverage in Thomson Reuter’s productsand services. Beginning with V. 6(1) 2013, IJABE will be indexed and abstracted in:♦ Science Citation Index Expanded (also known as SciSearch®)♦ Journal Citation Reports/Science Edition♦ Current Contents®/Agriculture, Biology, and Environmental Sciences♦ Biological Abstracts♦ BIOSIS Previews